(untitled) (Journal of the College of Basic Education, 2022)
The Turkish military institution is one of the strongest and most organized institutions of the Turkish stateIf it is not, in fact, a supreme authority that lies above the constitution and other state institutions, including bodieselected; This institution derives its importance and strength from the tight internal organization of this institutionIt enjoys complete independence in selecting its leadership elements and has a clear vision of its rolethe supreme goals of the state; In addition to the huge numerical strength of the Turkish Armed Forces ©So that it comes according to this criterion in the second place after America among the NATO countries. Over time, the military was able to establish a non-military elite in the countrybureaucracy and intellectuals;